Comparison of short‐term outcomes and perioperative costs in laparoscopic versus robotic surgery for rectal cancers: A real‐world cohort study using Japanese nationwide inpatient database - Hiroki Hamamoto; Masato Ota; Takafumi Shima; Toru Kuramoto; Kazuya Kitada; Kohei Taniguchi; Mitsuhiro Asakuma; Yasuhiro Oura; Yuri Ito; Sang‐Woong Lee (Annals of Gastroenterological Surgery)
Abstract Aim Many studies have revealed the benefits of robotic surgery for rectal cancer; however, real‐world data are insufficient. This study aimed to compare the short‐term outcomes and perioperative costs of laparoscopic and robotic surgery for rectal cancer using a real‐world database. Methods The data of patients who underwent laparoscopic or robotic surgery for rectal cancer between January 2018 and January 2021 from a nationwide Japanese inpatient database provided by Medical Data Vision Co., Ltd. were analyzed. We performed propensity score matching (PSM) analysis to compare the in‐hospital mortality, morbidity, readmission rate, reoperation rate, length of postoperative stay, and medical costs between the two groups. Results We performed PSM analysis on 18 952 eligible patients. After PSM, 1396 patients in the laparoscopic group and 1396 in the robotic group were compared. The robotic group had a lower surgical site infection rate (2.9% vs. 1.5%, p = 0.010), lower respiratory failure rate (1.3% vs. 0.6%, p = 0.049), and higher operative medical costs (1 291 371 vs. 1 312 462 JPY, p = 0.013). The total medical costs of the two groups were comparable (1 862 439 vs. 1 895 822 JPY, p = 0.051). Conclusions PSM analysis revealed that robotic surgery was associated with better outcomes than laparoscopic surgery in terms of surgical site infection and respiratory failure rates. The operative medical costs of robotic surgery were significantly higher than those of laparoscopic surgery. However, there was no significant difference in the total medical costs between robotic and laparoscopic surgery for rectal cancer.